Dangerous diagnostics? Regulatory reform in the genomic era. (19th February 2019) - Holloway, Kelly; Miller, Fiona A; Gutierrez, Alberto; Hogarth, Stuart
Abstract : Molecular diagnostics are expanding rapidly yet many have not been externally evaluated. Kelly Holloway and colleagues identify failings in the regulatory system and report on recent efforts at reform